Molecular characterization of Ethiopian indigenous goat populations: Genetic diversity and structure, demographic dynamics and assessment of the kisspeptin gene polymorphism - Mekuriaw, Getinet (Addis Ababa University, 2016)
Ethiopia lies within the earliest geographic center for the dispersal of livestock into the African continent. It therefore comprises a unique repository of livestock genetic diversity in the continent. However, information relating to the origin and divergence of domestic goats in the North-East African region, and Ethiopia in particular, remains unknown despite the availability of genomic tools to assess the same. Here, the complete mitochondrial DNA D-loop region of 309 individuals representing 13 Ethiopian indigenous populations of goats was sequenced to investigate the maternal historical demographic dynamics of Ethiopian indigenous goats. Similarly, genotype data were generated from 14 populations by the 50K Caprine SNP CHIP array to investigate the genetic diversity and structure of Ethiopian indigenous goats. The Chinese Cashmere, Cashmere-Ibex hybrid and the wild Swiss Alpine Ibex populations were also included as outgroup for comparison. In addition, analysis of polymorphism of the KISS1 gene and its association with litter size, and haplotype and patterns of linkage disequilibrium (LD) analysis were conducted in exon regions of the kisspeptin gene of Gondar and Woyto-Guji goat populations. A total of 173 and 242 Sanger sequences were employed for further analysis of exon1 (1210 bp) and exon2 (325 bp) regions of the kisspeptin gene, respectively. Sequencing of the mtDNA, 174 variable sites that generated 231 haplotypes were observed in the D-loop region of mtDNA sequences and these haplotypes defined two haplogroups lacking a phylogeographic structure but with a high genetic diversity. In a combined analysis of reference haplotypes representing the six globally defined Caprine haplogroups revealed out two haplogroups to be A and G, with the former being the most predominant. The lack of phylogeographic structure and a weak population differentiation (overall FST = 0.0245) suggest extensive gene flow amongst indigenous Ethiopian goats. In the genome wide survey, high genetic diversity (HE ≥ 0.35) but low level of genetic differentiation among the populations is revealed. The 14 populations were grouped into six clusters and none of them was specific to one population or geographic region. Interestingly, population phylogenetic analysis did not support the classification of Ethiopian goats based on their agro-ecological location, associated production system and phenotypic family as suggested previously, but differentiated the Kaffa goat from the rest of 13 Ethiopian goat populations. Based on the admixture and phylogenetic network analyses, the 14 Ethiopian goat populations can be re-grouped into seven goat types. On the other hand, polymorphism analysis of the KISS1 gene revealed five complete substitutions and 15 polymorphic sites in both exon regions. The overall average HE was 0.18863±0.21 for exon1 and 0.03155±0.01 for exon2. Among detected polymorphic sites only four SNPs contributed 18%-31% multiple birth. Similarly, a total of 29 and three haplotypes were detected in exon1 and exon2, respectively. The overall haplotype diversity was 0.8703 for exon1 and 0.0703 for exon2. Lowest (0.083 for Woyto-Guji and 0.081 for Gondar goats) and modest (0.656 for Woyto-Guji and 0.635 for Gondar goats) average estimates of R2 and |D’| were obtained in LD decay analysis in exon1, respectively, and most of the R2 and |D’| values suffer floor and ceiling effects. The neutrality tests showed significant and negative values of FS for Woyto-Guji (FS = -8.098) and for Gondar goats (FS = -12.08); whereas, the Tajima’s D test was positive and non-significant. Overall, there was high goat population dynamics that caused to have highest level of population admixture.